On use of the derivational concept of law interpretation in resolving criminal law issues (Ius Novum, 2021)
The principal aim of the study is to present the possibility of using the derivational concept of interpretation of the law to solve several selected significant problems of criminal law – on the basis of the two levels of legal text adopted according to the concept in question and the substantive fragmentation of norms in legal regulations. Against this background, it has been established that every provision typifying the specific section of the Penal Code always expresses out the foundations of a sanctioned and sanctioning norm, which means that criminal law is a regulator of social life and an inherent source of sanctioned (forbidding) norms. Moreover, it has been established that the provisions defining justification in law are, in fact, modifying provisions and are not the basis for reconstructing a specific legal norm. They constitute an indispensable component of sanctioned norms and modify their scope of application. As a result, in the area of criminal law, the determination of the unlawfulness of an act is always of a definitive nature, because overstepping a specific sanctioned norm implies unlawfulness. Thus, it is not the case that the statutory definiteness of an act and its unlawfulness are two different elements of the structure of an offence, located on different levels of that structure.
Keywords: interpretation of the law; sanctioned norm; unlawfulness; justification in law; definiteness of a prohibited act